Fermented Cocoa Beans (Theobroma cacao L) in Southeast Aceh District - Tambunan, Syariani; Sebayang, Nico Syahputra; Sari, Desi Sri Pasca (Altifani Journal: International Journal of Community Engagement, 2021)
One of the productions of the agricultural industry that has a fairly high foreign exchange value for our country is cocoa, but our cocoa production is still of low quality. To get good quality cocoa, good processing must be done. Fermentation of cocoa beans is one way to improve the quality of cocoa so that it can be sold in national and international markets. The purpose of this activity is to help cocoa farmers, especially in Southeast Aceh district, in improving the quality of cocoa production, so that the cocoa products of Southeast Aceh farmers can compete in trade both locally and abroad. The implementation of this activity is carried out through training to improve the quality of cocoa. There are several activities, namely: Sorting Cocoa, peeling cocoa pods, fermenting cocoa pods for 5 days and the last step is drying until the moisture content of cocoa pods reaches 7%. The result of this activity is to increase the knowledge of cocoa farmers in Southeast Aceh Regency in order to improve the quality of cocoa beans, so that cocoa sales can be accepted and compete in the market.